2017
DOI: 10.1371/journal.ppat.1006475
|View full text |Cite
|
Sign up to set email alerts
|

Host-derived apolipoproteins play comparable roles with viral secretory proteins Erns and NS1 in the infectious particle formation of Flaviviridae

Abstract: Amphipathic α-helices of exchangeable apolipoproteins have shown to play crucial roles in the formation of infectious hepatitis C virus (HCV) particles through the interaction with viral particles. Among the Flaviviridae members, pestivirus and flavivirus possess a viral structural protein Erns or a non-structural protein 1 (NS1) as secretory glycoproteins, respectively, while Hepacivirus including HCV has no secretory glycoprotein. In case of pestivirus replication, the C-terminal long amphipathic α-helices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…We generated CEACAM1 knockout (KO) Huh7.5.1 cells using the CRISPR/Cas9 system according to previously described methods . We confirmed CEACAM1 deficiency in monoclonal cells by flow cytometry and enzyme‐linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…We generated CEACAM1 knockout (KO) Huh7.5.1 cells using the CRISPR/Cas9 system according to previously described methods . We confirmed CEACAM1 deficiency in monoclonal cells by flow cytometry and enzyme‐linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…Family Flaviviridae consists of four genera, Flavivirus , Hepacivirus , Pegivirus , and Pestivirus (Fukuhara et al 2017 ). The genomes of Flaviviridae viruses commonly contain a single-strand positive RNA encoding a polyprotein which will be cleaved into 2–4 structural proteins and 7–9 non-structural proteins (Chambers et al 1990 ).…”
Section: Families Unassigned To Any Ordermentioning
confidence: 99%
“…In addition, we showed that NS1 participates in the formation of HCV and CSFV particles but not in the replication of viral RNA. 49 Collectively, these data suggest that NS1 plays a dual role in the formation of replication complexes and infectious particles via different mechanisms.…”
Section: Host-and Virus-derived Secretory Glycoproteins In the Formatmentioning
confidence: 96%
“…By contrast, Akey et al showed that NS1 mutants which are unable to generate replication complexes are nonetheless capable of remodeling the membranes of liposomes. In addition, we showed that NS1 participates in the formation of HCV and CSFV particles but not in the replication of viral RNA . Collectively, these data suggest that NS1 plays a dual role in the formation of replication complexes and infectious particles via different mechanisms.…”
Section: Comparable Roles Of Host‐ and Virus‐derived Secretory Glycopmentioning
confidence: 96%
See 1 more Smart Citation